Half integer values of order-two harmonic numbers sums - Sofo, A. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
Half integer values of harmonic numbers and reciprocal binomial coefficients sums are investigated in this paper. Closedform representations and integral expressions are developed for the infinite series.